Efficacy of cervical spine muscle strength training in the prevention of cervical spine injuries in hockey players: A critically appraised topic - Costa, C. (International Journal of Strength and Conditioning, 2021)
From 1948 through 2011, 355 documented cases of spinal cord injuries to were reported in ice hockey players, of which 78.9% were indicative of damage to the cervical spine. Tyrakowski and colleagues report a high incidence of cervical spine injuries occur during contact sports, such as football and hockey.6 In contrast, additional evidence purports that contact sports injuries only represent 8.9% of total spinal cord injuries reported annually. Hockey presented a particularly high incidence of spinal cord and cervical spine injuries. Therefore, the goal of this brief review is to examine how muscle strength of the neck, cervical stabilization and range of motion (ROM) impacts cervical spine injuries. Additionally, acquiring a baseline strength analysis may elucidate the propensity towards neck related injuries in hockey players. A collection of baseline ROM should be collected at the beginning of each season and used to measure percent baseline scale. The percent baseline scale could be used to delineate the percentage of return to baseline for the purpose of understanding an appropriate timeline.